Implementasi Fuzzy Time Series Logika Singh Untuk peramalan Nilai Ekspor Nilam di Indonesia - Putri, Rahmadita Amalia; Subhan, Muhammad (Journal of Mathematics UNP, 2025)
Patchouli is used as one of the mixtures of cosmetic products, food industry, paint making, aromatherapy, and various other industrial needs and is needed by various types of industries in various countries. Due to the high world demand for patchouli, a prediction is made to anticipate uncertainty so that an estimate is obtained that is close to the actual situation. The method that can be used is the Singh logic fuzzy time series method. This research is an applied research, where the data taken is the data on the value of patchouli exports in Indonesia in the period January 2020 to July 2024. The results of forecasting the value of patchouli export data in Indonesia with this method are then measured for accuracy using MAPE. From the Singh logic fuzzy time series forecasting method, the MAPE obtained was 7,215%. Based on the MAPE, forecasting export value in Indonesia with Singh's fuzzy time series logic has a very good level of accuracy. For the following period, the export value of patchouli is projected to be US$ 29,638,657.15 for August 2024, US$ 28.212.795,11 for September 2024, and US$ 28.277.533,23 for October 2024. The Predicted value is categorized qith a very high export value of patchouli.